PSYCHOLOGICAL DISTANCE AS A BARRIER TO EFFECTIVE INTERACTION BETWEEN TEACHER AND STUDENT - Hulkar Mirkosimova (Modern American Journals, 2025)
This article examines psychological distance as a barrier to effective interaction between teachers and students in the context of higher education. Psychological distance, defined as the perceived emotional, cognitive, or social gap between individuals, can significantly influence communication, trust, and learning outcomes in the educational environment. The paper explores the theoretical foundations of psychological distance, its manifestations in pedagogical practice, and its impact on student engagement, motivation, and academic performance. Attention is given to cultural and institutional factors that contribute to this distance, particularly in the context of Uzbekistan’s educational system. The article also suggests strategies for reducing psychological distance and fostering more empathetic, inclusive, and productive teacher-student relationships. The findings underline the importance of emotional closeness, openness, and mutual respect in building effective educational communication.
Keywords: Psychological distance, educational communication, teacher-student interaction, emotional barrier, pedagogical relationship, trust, learning effectiveness, higher education, empathy, classroom dynamics.